3D Hydrangea‐like InVO4/Ti3C2Tx Hierarchical Heterosystem Collaborating with 2D/2D Interface Interaction for Enhanced Photocatalytic CO2 Reduction. Issue 7 (28th April 2021) - Li, Liang; Yang, Yong; Yang, Liuqing; Wang, Xiaoyong; Zhou, Yong; Zou, Zhigang
Abstract: 3D hydrangea‐like InVO4 /Ti3 C2 Tx heterosystem is fabricated by in‐situ growth of InVO4 on Ti3 C2 Tx and on spot self‐assembly. The formation of a hierarchical architecture collaborating with well‐defined 2D/2D interfacial interaction is constructed by optimizing the ratio of Ti3 C2 Tx incorporated in the formation of InVO4 . The as‐obtained InVO4 /Ti3 C2 Tx presents improved photon trapping capacity and exposure of reactive sites owing to the enhanced BET specific surface areas, and the capture capacity towards CO2 is strengthened coordinated with the basic feature of Ti3 C2 Tx . Based on DFT calculations, the electron transfer from InVO4 to Ti3 C2 Tx is demonstrated, and the unique 2D/2D interface interaction in InVO4 /Ti3 C2 Tx heterosystem efficiently improves the separation of photogenerated charge carriers. As a result, the 3D hierarchical InVO4 /Ti3 C2 Tx heterosystem presents 13.83 μmol g −1 h −1 of CO production (3.1‐folds of pristine InVO4 ) with 92% selectivity and superior stability. The 3D hierarchical design collaborating with 2D/2D interfacial interaction provides a new avenue to develop ideal catalysts for artificial photosynthesis. Abstract : 3D hydrangea‐like InVO4 /Ti3 C2 Tx hybrid in collaboration with 2D/2D interface is developed via an in‐situ growth process and on spot self‐assembly, contributing to efficient and selective photoconversion towards CO2 .